Community Moral Solidarity as a Mediator of the Impact of Family Disruption on Adolescent Behavior - Injilia Watupongoh; Hamsah Hamsah; Sangputri Sidik (Citra Media Publishing, 2026)
Changes in family structure and function resulting from prolonged conflict, economic hardship, and parental separation are often associated with increased vulnerability to juvenile delinquency. However, this relationship is not deterministic and is significantly shaped by broader community dynamics. This study aims to examine how community moral solidarity mediates adolescents’ experiences of family disruption in Talete Satu Village, Tomohon Tengah District. The research employs a qualitative approach with an intrinsic case study design grounded in an interpretive paradigm. Data were collected through in-depth interviews with 13 adolescents from 8 families, complemented by 6 community informants and contextual observations. First, family disruption generates ambivalent emotional regulation among adolescents, manifested in feelings of insecurity, loneliness, and occasional rebellious behavior, though not necessarily leading to deviance. Second, adolescents demonstrate differentiated responses to family conditions, with some engaging in risk behaviors while others develop adaptive coping strategies through social and religious participation. Third, community moral solidarity functions as an informal social control mechanism by providing normative support, social monitoring, and collective expectations that shape adolescents’ behavioral orientations. These findings suggest that family disruption alone does not determine juvenile delinquency. Rather, the interaction between familial experiences and the structure of community moral solidarity shapes behavioral outcomes.